Development of Quadcopter Drone and IoT Module Technology in Geospatial-Based Air Emission Monitoring - Hapsari, Anindya Ananda; Vresdian, Devan Junesco; Dionova, Brainvendra Widi; Andreansyah, Teddy (Journal of Artificial Intelligence and Software Engineering, 2025)
his research introduces an innovative drone-based air quality monitoring system, equipped with multi-parameter sensors to measure temperature, humidity, CO2 concentration, and PM2.5 in real-time. The system is designed with integration to the Internet of Things (IoT), enabling direct data transmission to smart devices for instant access and quick analysis. This system provides a practical solution for monitoring air quality flexibly, especially in areas that are difficult to reach with conventional monitoring devices. Simulations showed that the drone canoperate for 4.8 to 14.77 minutes with an 80% battery depletion, depending on environmental conditions. Calibration testing of the sensors showed high accuracy, although data variations were significantly affected by temperature changes. The system underwent trial and calibration as an initial step to ensure device reliability and open opportunities for broader application development, including air quality monitoring in urban areas, industrial zones, and natural environments. The main advantage of this system lies in its ability to provide real-time data and flexibility in data collection from various locations. However, the study also identified several challenges, such as battery capacity limitations and communication range, which will be the focus of further development. Potential improvements include optimizing battery capacity, expanding communication range, and developing predictive